Pengaruh Gaya Belajar Terhadap Prestasi Belajar Mahasiswa Program Studi Pendidikan Matematika (IAIM NU) Metro - Widyawati, Santi (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
Learning style is one of the factors that allegedly affect the learning achievement (GPA) of Mathematics Education Mathematics Program of Maarif Nahdatul Ulama Institute of Islamic Studies. The purpose of this research is to know